Rhynchophorus palmarum used in traditional medicine in the peruvian Amazon - Delgado Vásquez, César (2019)
Ethnoentomological research focuses on the wealth of knowledge about insects used by indigenous communities. Here, we examine the medicinal use of insects, with a particular focus on Rhynchophorus palmarum, also known as suri, by indigenous peoples in the Peruvian Amazon. Between January 2014 and November 2015, a semi structured survey was conducted in six communities belonging to Kukama Kukamiria, Tikuna, and Awajún ethnic groups. Each participant answered three key questions: i) what insects do you use to treat your diseases; ii) what diseases do you treat; and iii) how do you treat each disease? A total of 63 people were interviewed. Over half of the interviewees from the three ethnic groups mentioned using the larva of the R. palmarum for medicinal purposes. The oil of the larva is used to treat more than ten diseases, particularly respiratory illnesses. Chemical analysis of the larvae indicates the presence of linoleic and linolenic acids, which confer antimicrobial and anti-inflammatory properties.